Macromol. Mater. Eng. 5/2017. Issue 5 (May 2017) - Ye, Qiang; Spencer, Paulette; Yuca, Esra; Tamerler, Candan
Abstract : Front Cover: Engineered peptide is utilized to induce remineralization of deficient dentin matrices for integrated biomaterials–tissue interface design. The distribution of mineral throughout the interface following the peptide‐mediated remineralization is confirmed by Raman spectral images. This is reported by Qiang Ye, Paulette Spencer, Esra Yuca, and Candan Tamerler, in article number1600487 .